Parametrização dimensional, por modelo de regressão, de próteses de mão para crianças, confeccionadas por manufatura aditiva - (:unkn) unknown (Universidade Federal de Goiás, 2016)
The use of artificial limbs provides great improvements in the quality of life of people who were born with malformation or have lost their upper limbs. However, the value of conventional prostheses is not accessible to the majority of the population. In order to change this reality, began to emerge projects using additive manufacturing. The use of such technology allows the manufacture of more accessible and customized prostheses. However, the adequacy of project design is still a problem, due to the lack of data on the size of the upper limbs, especially on children and adolescents. Based on this need, this work seeks to find a way to parameterize the hand dimensions, thus helping in the better dimensioning of the prostheses. Thus, this work looks for a variable that presents satisfactory correlation with the dimensions of the upper limb. After finding such a relationship, a table and a parametric model were created that can estimate the length of the hand from the height.
Dimensional parameterization, by regression model, of hand prostheses for children, made by additive manufacture
Keywords: Prótese de mão; Membro superior; Criança; Antropometria; Modelo de regressão; Hand prosthesis; Upper limb; Children; Anthropometry; Regression model; CIENCIAS EXATAS E DA TERRA